Incommensurate crystal growth behavior in strontium titanate glass ceramic system - Thakur O.P.; Kumar D.; Parkash O.M.; Pandey L. (My University, 2025)
Crystals with different faceting behavior were observed in the strontium titanate borosilicate glass ceramic system with a small amount of bismuth oxide addition and proper heat treatment schedule. These types of faceting morphology were generally observed in phase-separated glasses followed by heterogeneous nucleation. X-ray diffraction and electron microscopic techniques were used to characterize these samples. X-ray diffraction patterns for bulk and pulverized samples were observed to be readily different from each other. Peaks in the X-ray diffraction pattern for bulk samples can be indexed for icosahedral symmetry.